Optimization of the economical indexes of automotive Diesel engines in the regimes of partial loads and empty - Lira Cacho, Guillermo (1999)
This theoretical - experimental investigation mainly focuses: The particular running processes of diesel engines at partial and idle loads and, the simplest and most effective method to improve these running parameters, specially economical indexes. According to our investigation results, this method is the initial fuel pressure regulation in the high pressure line; from the feed line (low pressure) and, by means of the initial pressure regulation valve (RND valve, russian origin). This is an interesting system, owing to it is applicable to diesel engines with separated injection systems, which are being operated and, maintains practically its original fuel system structure. Its application lets to supply additional fuel to the high pressure line, taking advantage of the hydrodynamic phenomenon, which occurs after each injection ending and so that, intensify the injection processes and, improve the atomizing, fuel-air mixture forming and combustion processes. The experimental assays were developed at Cussons test stand with Ricardo E6 engine of the Institute of internal combustion engines of the National Engineering University. We shall show some comparative results of this research.